Intercultural Pragmatics (De Gruyter Mouton, 2004)
Intercultural Pragmatics is a fully peer-reviewed forum for theoretical and applied pragmatics research. The journal promotes the development and understanding of pragmatic theory and intercultural competence by publishing research that focuses on general theoretical issues, more than one language and culture, or varieties of one language, while making a special effort to cross disciplinary boundaries.